Genome Analysis and Transcriptomic Profile of Ectomycorrhizal Fungus Pisolithus albus under Metal Stress - Chot, Eetika (My University, 2024)
An ectomycorrhizal fungus Pisolithus albus establishes the natural symbiosis with plant roots on extreme heavy metal (HM)-rich soil. Based on its ecological importance and lack of genomic reports, the current study has conducted the whole-genome sequencing of Indian P. albus using the Illumina HiSeq X platform to explore genomic patterns and traits possibly attributing to its specialization. The sequenced reads were de novo assembled into 14585 scaffolds with 49.29% of GC content and 91.8% of BUSCO completeness. A genome assembly was predicted with 23,035 protein-coding genes accounting for 44.1% of total genome length and 612 non-coding RNA genes. In extensive annotation against different databases, 56.1% of gene models were assigned with gene ontology terms. The genome-wide sequence alignment determined the close phylogenetic association of P. albus with Pisolithus microcarpus. The comparative analysis of protein sequences among 3 Pisolithus species identified 49.12% shared; and 11.25% (P. albus), 10.33% (Pisolithus tinctorius), and 8.81% (P. microcarpus) unique basic functional and stress adaptation associated orthologous clusters. The HM tolerance potential largely varies among the different isolates of the same Pisolithus species. In the past decade, numerous reports pointed to the challenge of selecting compatible fungal isolates for bioremediation of specific metal-polluted sites. Hence, the study aimed to understand P. albus key genes and pathways behind its metal tolerance and its distinct transcriptome response to single or multi-metal stress in high and low concentrations. At 480 µM Cu and 16 µM Cd toxic concentrations, P. albus has shown survival and accumulated 1.46 µg Cu and 1.13 µg Cd per mg of dry mycelia respectively. Therefore, this study has conducted the whole transcriptome profile of P. albus under 240 µM Cu (MSR1), 8 µM Cd (MSR2), 240 µM Cu + 8 µM Cd (MSR3), and 80 µM Cu + 4 µM (MSR4) stress. The study found a stronger response of P. albus to single-metal stress in high concentration as compared to multi-metal stress in relatively lower concentrations suggesting the “metal concentration” as a primary determining factor behind the intensity of fungal response. MSR1 and 4 commonly shared the highest number of 2,933 (29.9%) differentially expressed genes (DEGs) whereas MSR2 and 3 shared the lowest DEGs number of 1,568 (16%). The strongest fungal response was found under MSR3 with the induction of some unique genes associated with tolerance induction, detoxification, DNA repair, methionine biosynthesis and trehalose synthesis. Besides a considerable difference obtained in a fungal response against different stress treatments, cell wall modification, membrane protection, anti-oxidant defense, differential expression of metal transporters, and heat shock proteins were found common in all stressed samples. The current study would critically contribute to understanding fungal HM tolerance and its successful utilization in the rehabilitation programs of metal-contaminated abandoned lands. The positive correlation of RNA-sequencing and RT-qPCR deduced fold change values of selected genes (Pearson’s correlation coefficient R2 value of 0.7531) showed the high credibility of the presented data.
Ph.D thesis
Keywords: Pisolithus albus; Genome analysis; Transcriptomic analysis; Bioremediation; Metal stress